A rare NAB2ex6::STAT6ex3 fusion identified in a large pelvic epithelioid and cystic high-risk solitary fibrous tumor (SFT) - Nandi, Jhuma; Peeples, Mary; Stephenson, Ruth D.; Gottshall, Lauren; Ghodoussipour, Saum; Becker, Murray; Riedlinger, Gregory M.; Li, Lin (Human Pathology Reports, 2025)
Solitary Fibrous Tumour (SFT) is a fibroblastic mesenchymal neoplasm with variable clinical behaviour with a genetic hallmark of recurrent fusion of NAB2 and STAT6 genes. More than 40 fusion variants have been reported and the NAB2ex6::STAT6ex16/17 groups have been found to carry significant higher risk of recurrence. We reported here a rare NAB2ex6::STAT6ex3 fusion found in a large pelvic epithelioid and cystic high risk SFT in a 65-year-old women. Significantly the molecular findings in our patient correlate with the patient’s clinical-pathological high-risk features, expanding the landscape of our knowledge of SFT.